Analisis SWOT Sebagai Dasar Perumusan Strategi Bersaing Bisnis Tour and Travel Pada PT Cidi Young Asian Padang - Dinda Edisha Putri; Yofina Mulyati (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2025)
This research aims to analyze the business competitive strategy at PT Cidi Young Asian Padang. This research is entitled "SWOT analysis as a basis for formulating competitive strategies for the tour and travel business at PT Cidi Young Asian Padang". using SWOT analysis to identify internal and external factors that influence the company's competitiveness.The method used is descriptive qualitative, with data collection techniques through observation, interviews and documentation. Analysis is carried out using the IFE, EFE, SWOT, CPM and QSPM matrices to formulate the most effective strategy.The research results show that PT Cidi Young Asian has strong internal factors IFE3.43 and is able to respond well to opportunities and overcome threats EFE 3.28. Based on the IE Matrix, the company is in Quadrant I (Grow & Build), indicating a strong position with great opportunities for growth. In addition, the CPM Matrix confirms the company's excellence in responsive service, flexibility of tour packages, and extensive vendor network.The main strategy recommended is market penetration, with the highest score in the QSPM Matrix (7.58). This strategy includes increasing digital marketing, expanding business partner cooperation, and improving customer service. By implementing this strategy, PT Cidi Young Asian is expected to increase its competitiveness and business growth in the travel industry.